Governing guns, preventing plunder international cooperation against illicit trade - Efrat, Asif. (New York ; Oxford : Oxford University Press, 2012)
From human trafficking to smuggling small arms to looting antiquities, illicit trade poses significant threats to international order. So why is it difficult to establish international cooperation against illicit trade? This book offers a novel, thought-provoking answer to this crucial question.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (viewed on July 16, 2012).
Keywords: Smuggling -- Prevention -- International cooperation; Illegal arms transfers -- Prevention; Human trafficking -- Prevention; Classical antiquities thefts -- Prevention